Dithiocarbazate ligands and their Ni(II) complexes with potential biological activity: Structural, antitumor and molecular docking study - Cavalcante, Cássia de Q. O.; da Mota, Tales H. A.; de Oliveira, Diêgo M.; Nascimento, Érica C. M.; Martins, João B. L.; Pittella-Silva, Fabio; Gatto, Claudia C. (Frontiers in Molecular Biosciences, 2023)
In the search for new metal complexes with antitumor potential, two dithiocarbazates ligands derived from 1,1,1-trifluoro-2,4-pentanedione (H2L1 and H2L2) and four Ni(II) complexes, [Ni(L1)PPh3] (1), [Ni(L1)Py] (2), [Ni(L2)PPh3] (3) and [Ni(L2)Py] (4), were successfully synthesized and investigated by physical-chemistry and spectroscopic methods. The crystal structure of the H2L1 and the Ni(II) complexes have been elucidated by single-crystal X-ray diffraction. The obtained structure from H2L1 confirms the cyclization reaction and formation of the pyrazoline derivative. The results showed square planar geometry to the metal centers, in which dithiocarbazates coordinated by the ONS donor system and a triphenylphosphine or pyridine molecule complete the coordination sphere. Hirshfeld surface analysis by dnorm function was investigated and showed π⋅⋅⋅π stacking interactions upon the molecular packing of H2L1 and non-classical hydrogen bonds for all compounds. The fingerprint plots showed the main interactions attributed to H⋅⋅⋅H C⋅⋅⋅H, O⋅⋅⋅H, Br⋅⋅⋅H and F⋅⋅⋅H, with contacts contributing between 1.9% and 38.2%. The mass spectrometry data indicated the presence of the molecular ions [M+H]+ and characteristic fragmentations of the compounds, which indicated the same behavior of the compounds in solution and solid state. Molecular docking simulations were studied to evaluate the properties and interactions of the free dithiocarbazates and their Ni(II) complexes with selected proteins and DNA. These results were supported by in vitro cytotoxicity assays against four cancer cell lines, showing that the synthesized metal complexes display promising biological activity.